2019
DOI: 10.1002/fsn3.1106
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate peel extract alters the microbiome in mice and dysbiosis caused by Citrobacter rodentium infection

Abstract: Treatment of mice with a pomegranate peel extract (PPX) decreased the pathogenicity of Citrobacter rodentium ( Cr ) infections. Here, we investigate the effects of PPX on the microbiome of uninfected or Cr ‐infected C3H/HeNCr mice by 16S rRNA gene sequencing. Mice were treated with water or PPX for 14 days, feces were collected, and then, the mice were infected with Cr and feces collected again at day 6 postinfection. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
(94 reference statements)
1
19
1
Order By: Relevance
“…Well known health promoting phytochemicals such as green tea and black tea polyphenols may regulate host health through promoting the growth of Bacteroides while suppressing the growth of Firmicutes [33]. Another study also showed that pomegranate peel extract treatment for 14 days significantly reduced F/B ratio in mice [34]. In our study, we also observed a significantly lower F/B ratio in BC-fed mice than the control mice.…”
Section: Discussionsupporting
confidence: 79%
“…Well known health promoting phytochemicals such as green tea and black tea polyphenols may regulate host health through promoting the growth of Bacteroides while suppressing the growth of Firmicutes [33]. Another study also showed that pomegranate peel extract treatment for 14 days significantly reduced F/B ratio in mice [34]. In our study, we also observed a significantly lower F/B ratio in BC-fed mice than the control mice.…”
Section: Discussionsupporting
confidence: 79%
“…The use of pomegranate peel extracts on the outcome of coccidiosis in mice has been found to attenuate inflammation and injury of the jejunum that is induced by Eimeria papillata infections [83]. In a similar study, treatment with a pomegranate peel extract decreased the pathogenicity of Citrobacter rodentium infections in mice, suggesting an alteration of the microbiome, making it more resistant to Citrobacter rodentium [82]. Citrobacter rodentium mimics many aspects of human enteropathogenic Escherichia coli infections and is therefore used in several studies with mice.…”
Section: Prevention and Treatment Of Infectionsmentioning
confidence: 93%
“…Furthermore, punicalagin reduces the high-fat diet-induced accumulation of cardiac triglyceride and cholesterol in obese rats via adenosine monophosphate (AMP)-activated protein kinase (AMPK) activation [81]. Finally, pomegranate leaf extracts can inhibit lipid absorption and reduce blood triglycerides and total cholesterol in hyperlipidemic mice by inhibiting lipase activity [82].…”
Section: Derivativementioning
confidence: 99%
“…Of note, there were two OTUs assigned to the genus Citrobacter while seven OTUs were assigned to the genus Trabulsiella (and four of them annotated to T. farmeri) using the Greengenes database in this study. The European Nucleotide Archive suggests that the Greengenes assignment of Trabulsiella may be incorrect [31]. The representative sequences of the OTU involved also mapped to Citrobacter in the Ribosomal Database Project database but at a 90% similarity level.…”
Section: Validation Of Pro-resolving Properties Of Krill Oil and Its mentioning
confidence: 99%